Slovakia: Traditions and New Challenges of Labor Law - Dolobáč, Marcel (Fundamentals of Labor Law in Central Europe, 2022)
This chapter consists of three basic sections. The first part provides an interpretation of the position of labor law in the legal system, based on the system of labor law itself, the subject of regulation, and the method thereof. The second part analyzes the employment contract, the collective agreement, and the relationship between these agreements, pointing out the selected issues in practice. Finally, the third part is a reflection on the direction of labor law in the context of social changes that occur with the onset of technological boom. Keywords: status of labor law, contractual freedom, subsidiarity of the Civil Code, employment contract, collective agreement, society 5.0